Ink in water : an illustrated memoir : or, How I kicked anorexia's ass and embraced body positivity! - Davis, Lacy J. (New Harbinger Publications, Inc., 2017)
"Lacy Davis's eating disorders begins with the germ of an idea: a seed of a thought that tells her she just isn't good enough. And like ink in water, the idea spreads. Blending bold humor, a healthy dose of self-deprecation, literary storytelling, and provocative artwork, Ink In Water is an unflinching, brutally honest look into Lacy"s mind as she learns to move past her self-destructive behaviors and toward a life of health, strength, and nourishment." -- Back cover.